A rare and forgotten diagnosis of gastrointestinal bleeding: primary aortoduodenal fistula. (14th March 2013) - Guner, Ali; Mentese, Umit; Kece, Can; Kucuktulu, Uzer
Abstract : Upper gastrointestinal (UGI) bleeding is a common medical condition among adults. Bleeding is mainly caused by the gastric or proximal duodenum, but rarely by the distal duodenum. Aortoduodenal fistula is one of the causes of UGI bleeding that results in a life-threatening condition if not treated properly. It is commonly observed in patients who have undergone previous aortic surgery and rarely occurs in patients without a history of aortic surgery. Diagnosis of aortoenteric fistula is difficult unless there is a high level of clinical suspicion. In this article, we aim to present a patient with aortoduodenal fistula and discuss the clinical presentation, as well as the diagnostic and therapeutic options of this disease.